Expanding Pharmacy Capacity for Patient-Centered Reproductive Health Services - Anna Pfaff; Sally Rafie (MDPI AG, 2020)
In the United States, patients face increasing practical barriers and concerns about stigma when seeking sexual and reproductive healthcare, specifically family planning services involving hormonal contraception, emergency contraception, and abortion. The pharmacist is a member of the interprofessional care team with the ability to provide non-judgmental, high-quality, and patient-centered care. The community pharmacy setting itself offers specific advantages which promote access, including availability in most neighborhoods, broad hours of operation, lack of need for an appointment, and a stigma-free space which is frequented for other goods and services. This commentary suggests specific ways for pharmacies to improve access to contraception, emergency contraception, and abortion in line with national quality recommendations. Particular focus is given to the intersection of sexual and reproductive health resources and referrals within the pharmacy profession as well as the training and technical assistance tools which can help address unmet patient need.